Gamma-aminoadamantane carboxylic acids : orientating building blocks in peptide chemistry - Wanka, Lukas; Justus Liebig University Giessen (My University, 2007)
The present thesis deals with gamma-aminoadamantane carboxylic acids. Allthough the simplest of these structural analogues of GABA were known for decades, no significant peptide chemistry has been disclosed. Therefore, improved syntheses of these compounds were worked out that allowed for facilitated syntheses of already known as well as new members of gamma-aminoadamantane carboxylic acids. Fmoc-/tert. butyl protective group chemistry was utilized to synthesize peptides incorporating the gamma-aminoadamantane carboxylic acids by using solution- as well as solid phase peptide synthesis (SPPS). Structural studies on these peptides were performed experimentally using NMR, IR and X-ray diffraction techniques, and theoretically with combined MM/DFT computations. The results of these studies suggest an orientating effect of the gamma-aminoadamantane carboxylic acids on the peptide chain, inducing turn-like adjustment of attached alpha peptide chaines. This was utilized in the synthesis of catalytically active peptides and novel peptide thiourea derivatives, that were successfully used in organocatalytic acylation reactions and Morita-Baylis-Hillman reactions. Preliminary tests showed activity of some compounds against Influenza A and blocking of the GABA transporter mGAT 1.

Die vorliegende Arbeit beschreibt gamma-Aminoadamantan Carbonsäuren. Obwohl die einfachsten Vertreter dieser Strukturanaloga von GABA seit Jahren bekannt waren, wurden sie bisher kaum als Peptidbausteine benutzt. Daher wurden verbesserte Synthesen ausgearbeitet, die die Darstellung der bekannten und einiger neuer Vertreter der ermöglichten. Fmoc-/tert. butyl-Schutzgruppenchemie wurde zur Synthese von Peptiden basierend auf gamma-aminoadamantan carbonsäuren sowohl in Lösung als auch an der festen Phase (SPPS) verwendet. Strukturuntersuchungen der neuartigen Peptide wurden experimentell mit spektroskopischen Methoden (IR, NMR, Röntgenstrukturanalyse) und theoretisch durch MM/DFT-Berechnungen durchgeführt. Diese Studien zeigen, daß die gamma-aminoadamantan carbonsäuren einen orientierenden Effekt auf alpha-Peptidketten ausüben und turnartige Konformationen induzieren. Dieser Effekt wurde ausgenutzt, um katalytisch aktive Peptide und neue peptidische Thioharnstoffderivate darzustellen, die in organokatalytischen Acylierungen und Morita-Baylis-Hillman Reaktionen verwendet werden. Vorläufige Tests zeigten ferner Aktivität einiger Derivate der gamma-Aminoadamantan Carbonsäuren gegen Influenza A Viren und blockierten den mGAT 1 Transporter.
Gamma-Aminoadamantan Carbonsäuren: Orientierende Bausteine in der Peptidchemie
Keywords: ddc:540